Motorbike-taxi-drivers as Infrastructure in the Indonesian City. Issue 3 (26th May 2020) - Peters, Robbie
ABSTRACT: This article explores how problems of inadequate urban transport and increasing underemployment in the large Indonesian city of Surabaya have been down-sourced to its men and their pedicabs, minivans and motorbikes. Motorbike-taxi-drivers have grown to around one-hundred-thousand over recent years, replacing pedicab and minivan drivers as Surabaya's iconic toiling men who traverse the city and keep its economy and people in motion. For these men, the city is a precarious place that puts them in traffic throughout the day, damaging their health yet providing them with much needed income. Such a city is unsustainable, yet functioning. It functions not simply because of the exploitability of these precarious underclass men, but because of their adaptability. Using historical and ethnographic detail, this article explores that adaptability through the ways those men use themselves and their vehicles to form an insurgent infrastructure from below that serves them as much as it serves the city.